ABC quality cost model: a case study - Silva Neto, José Alves (2019)
The purpose of this article is to show the advantage of introducing the ABC quality cost model in a small company in the field of machining and industrial tooling, how to manage production costs and, as a consequence, control its processes. To achieve the processes and/or products quality, not only the increase of costs needed to maintain the established quality level should be considered. The literature on this subject shows that quality programs, such as Total Quality Control, continuous improvement and other, in fact, decrease production costs, due to the elimination of rework and non-conformity of products delivered to customers, both internal and external. Moreover, any well-structured quality program is a fundamental element of survival, in today very competitive market. In order to develop a quality program, satisfying appropriate financial criteria, appropriate tools of quality cost management should be applied, supported by a continuous data collection system. This activity also requires the establishment of corrective actions, goals and objectives, evaluating the quality performance, in view of the expected results. By means of this case study, developed in a real company, it was possible introduce the costing model ABC to measure its quality costs, identifying and defining its main costs classification. Relevant sources of materials and operational waste generated, corrective and preventive action plans were identified and implemented, reducing by 76 % their quality costs over 12 months. It was concluded that the quality cost management in a small company similar to the one under an analysis, is an advantageous method for decision-taking, appropriate to leverage finance and minimize conformity deviations. After 36 months quality costs decreased further by about 92 %.